A randomised study comparing the effectiveness of acupuncture or morphine versus the combination for the relief of dyspnoea in patients with advanced non-small cell lung cancer and mesothelioma. (July 2016) - Minchom, A.; Punwani, R.; Filshie, J.; Bhosle, J.; Nimako, K.; Myerson, J.; Gunapala, R.; Popat, S.; O'Brien, M.E.R.
Abstract: Background: Dyspnoea is one of the commonest symptoms of lung cancer. Opioids can reduce dyspnoea. This study investigates acupuncture for relief of breathlessness in lung cancer. Methods: We performed a single-centre, randomised phase II study of 173 patients with non-small cell lung cancer or mesothelioma with dyspnoea score of ≥4 on visual analogue scale (VAS). Randomisation was to acupuncture alone (A), morphine alone (M) or both (AM). Acupuncture was administered at upper sternal, thoracic paravertebral, trapezius trigger points and LI4. Manubrial semi-permanent acupuncture studs were inserted and massaged when symptomatic. Arm A patients received rescue morphine. Primary end-point was proportion of patients achieving ≥1.5 improvement in VAS dyspnoea at 4 h. Measurements continued to day 14 and included VAS relaxation, line analogue rating (Lar) anxiety, hospital anxiety and depression and European Organisation for Research and Treatment of Cancer quality-of-life scores. Results: Dyspnoea VAS improved ≥1.5 in 74%, 60% and 66% of arms A, M and AM, respectively, and was maintained in 45% at 2 weeks. There was no statistically significant difference between arms. VAS relaxation improved in arms A (1.06 points) and AM (1.48 points) compared to arm M (–0.19 points, p  < 0.001). At 7 d, the Lar anxiety score improved in arm A (1.5 points), arm AM (1.2 points) and arm M (no change, p  = 0.003). Fewer patients received at least one morphine dose in arm A compared with arm M or AM (21% versus 87% versus 87%, respectively, p  < 0.001). Conclusions: A, M and AM were effective in relieving dyspnoea. Acupuncture relieved anxiety and was morphine sparing, providing an alternative to morphine. Highlights: This trial recruited 173 patients with non-small cell lung cancer or mesothelioma. Patients were randomised to acupuncture alone (A), morphine alone (M) or both (AM). Dyspnoea visual analogue scale improved ≥1.5 in 74%, 60% and 66% of arms A, M and AM, respectively. There was no statistically significant difference in dyspnoea control between arms. Acupuncture additionally relieved anxiety and acted as a morphine sparing treatment.